Le Hérisson dans le Brouillard de Youri Norstein : Rythmes et temporalités du film d'animation vers l'album illustré - Jérémy Pailler (Strenae)
Hedgehog in the Fog was an animated short film directed by the Russian filmmaker Yuri Norstein in 1975. It was adapted into a picture book for children, published in 2002. Sequences from the film were selected and reproduced in illustrated panels, faithful to the original aesthetic. They ordered the narrative thread. However, the passage from an animated medium to a "fixed" medium raises the question of the work’s form, as much as it redefines its content. The moving image is immobilized, the footage partitioned then distributed over a new format. The cutting of scenes, the reversal of the voice-over and text, the composition of the screen's frame against the page's frame: these adaptation methods multiply, problematizing the temporality of the original work and disrupting its reception. Limitations of the book format disturb the rhythm established in the film. The absence of movement, relief or sound forces the filmmaker to determine a new linearity. He rethinks the challenges of the screenplay, which until then had been unified by the dynamics of transforming plasticity. The hedgehog's adventure is a slow walk regulated by the artist's own doing: how can this complex rhythm be transposed into the book? Can the picture book be a space for reinventing temporalities characteristic of auteur animation? This article intends to shed light on these questions by adopting a position committed more to the filmic image than to the picture book. The recontextualized experience of the spectator-turned-reader also allows us to approach these problems from the point of view of reception.